2009
DOI: 10.1089/clo.2009.0003
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Embryo Culture Conditions for Increasing Efficiency of Cloning in Buffalo(Bubalus bubalis)and Generation of Transgenic Embryos via Cloning

Abstract: Cloning in bovine species is marred by low efficiency of blastocyst formation. Any increase in the efficiency of blastocyst formation upon nuclear transfer will greatly enhance the efficiency of cloning. In the present study, the effect of various media, protein sources, and growth factors on the development of cloned buffalo embryos was evaluated. Among various combinations tested, culture of cloned embryos in TCM-199 media on the feeder layer of Buffalo Oviductal Epithelial Cells (BOEC) in the presence of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…E mbryo culture environment is a crucial factor that affects embryo development in vitro, gene expression, and postimplantation development in the cultured mammalian embryos (Cheong et al, 2009;Wadhwa et al, 2009;Yamanaka et al, 2009a). The sensitivity of cloned embryos to culture environment was reported as higher than in vitro-fertilized or parthenogenetic (PA) embryos in terms of in vitro development (Yamanaka et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…E mbryo culture environment is a crucial factor that affects embryo development in vitro, gene expression, and postimplantation development in the cultured mammalian embryos (Cheong et al, 2009;Wadhwa et al, 2009;Yamanaka et al, 2009a). The sensitivity of cloned embryos to culture environment was reported as higher than in vitro-fertilized or parthenogenetic (PA) embryos in terms of in vitro development (Yamanaka et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…In several studies, it has been shown that the use of growth factors such as EGF and IGF-I improves the rate of blastocyst formation in IVF (Moreira et al , 2002; Wasielak & Bogacki, 2007) and SCNT embryos (Wadhwa et al , 2009; Wang et al , 2012). EGF improves oocyte maturation and increases the developmental potential of embryos.…”
Section: Introductionmentioning
confidence: 99%
“…Limited information has been available concerning the structural composition of ICM and TE cells in NT bovine embryos (Koo et al , 2002) except for some studies with IVF, parthenogenetic and in vivo embryos in the cow (Iwasaki et al , 1990; De la Fuente & King., 1997; Van de Velde et al , 1999). Although several reports have been available regarding the effect of IGF-1 and EGF on cell proportion in IVF embryos (Makarevich & Markkula, 2002; Sirisathien et al , 2003; Block et al , 2008; Wadhwa et al , 2009; Sakagami et al , 2012), very limited data exist for a similar effect by growth factors on NT bovine embryos (Wang et al , 2012). The objective of the present study was to investigate the effect of supplementing in vitro maturation and embryo culture media with IGF-I and EGF on oocyte maturation, embryo development and cell allocation in the NT bovine embryos.…”
Section: Introductionmentioning
confidence: 99%